ANALYSIS OF SOME ASSUMPTIONS OF NAVIER-STOKES EQUATION - Budarin V. (Problems of the Regional Energetics)
Several stages of the derivation of Navier-Stokes equations in coordinate form are analyzed. The purpose of the analysis is the determination of long-term problems of system closure, of reasons for differences of exact solutions for low Reynolds numbers and the appearance of unstable solutions using computer programs.